The information needs of adult cancer survivors across the cancer continuum: A scoping review. Issue 3 (March 2017) - Fletcher, Chloe; Flight, Ingrid; Chapman, Janine; Fennell, Kate; Wilson, Carlene
Highlights: Examined information needs of people diagnosed with cancer across the cancer continuum. The most frequently identified information needs related to treatment. Information needs varied across the continuum from diagnosis through to end of life. Information needs at recurrence, metastasis, and end of life are not well documented. Research needed to identify information needs at later stages of the cancer continuum. Abstract: Objective: To provide an updated synthesis of the literature that investigates the self-reported information needs of people diagnosed with cancer across the cancer continuum. Methods: We conducted a scoping review of the literature published from August 2003 to June 2015 and expanded an existing typology summarizing the information needs of people diagnosed with cancer. Results: The majority of the included studies ( n  = 104) focused on questions relevant to the diagnosis/active treatment phase of the cancer continuum (52.9%) and thus the most frequently identified information needs related to this phase (33.4%). Information needs varied across the continuum and the results highlight the importance of recognising this fact. Conclusion: People diagnosed with cancer experience discrete information needs at different points from diagnosis to survival. Much of the research conducted in this area has focused on their information needs during the diagnosis and treatment of cancer, and literature relating to information needs following completion of treatment is sparse. Practice implications: Further research is needed to discern the specific nature of the treatment concerns and identify the information needs that survivors experience during recurrence of cancer, metastasis or changes in diagnosis, and the end of life phase of the cancer continuum.